Ageing‐related changes in GABAergic inhibition in mouse auditory cortex, measured using in vitro flavoprotein autofluorescence imaging - Stebbings, K. A. (J Physiol, 2015)
Ageing is associated with hearing loss and changes in GABAergic signalling in the auditory system. We tested whether GABAergic signalling in an isolated forebrain preparation also showed ageing‐related changes. A novel approach was used, whereby population imaging was coupled to quantitative pharmacological sensitivity. Sensitivity to GABA(A) blockade was inversely associated with age and cortical thickness, but hearing loss did not independently contribute to the change in GABA(A)ergic sensitivity. Redox states in the auditory cortex of young and aged animals were similar, suggesting that the differences in GABA(A)ergic sensitivity are unlikely to be due to differences in slice health.